Logistic Regression Application in Determining Mode Selection Factors of Musi Emas Feeder Transport, Palembang City - Ismail, Ayu; Kadarsah, Edi; Agustien, Melawaty (ASTONJADRO, 2023)
Mode of transportation is absolutely a basic human need, especially in urban areas which tend to have high mobility. One type of mode that an important role in the urban transportation system is public transportation. oday, public transportation continues to make updates, one of which is public transportation in Palembang City marked by the start of operation of the Musi Emas feeder city transport in July 2022 with 7 routes. This study aims to identify the factors that influence and become the parameters of the traveling community in choosing mode of Musi Emas feeder city transportation Palembang City on the route corridor 1 Talang Kelapa – Punti Kayu, and corridor 2 Asrama Haji – Sematang Borang. The research approach used was quantitative with primary data sources from a revealed preference survey of 208 respondents who had used the Musi Emas feeder transport, and 192 respondents who had never used it. Analysis of the results of the survey data was modeled by logistic regression in order to look for factors that have an influence on choosing the mode of transportation of the Musi Emas feeder. The results of the analysis show that the independent variable data has a significant effect on variable dependent and the results of logistic regression analysis showed variable gender, age, and travel costs are influential variables in determining the choice of travelers to use the Musi Emas feeder city transportation mode.